Phenotypic and genotypic characteristics of Escherichia coli strains isolated during a longitudinal follow-up study of chronic urinary tract infections - Ulises Hernández-Chiñas; Ulises Hernández-Chiñas; Ricardo E. Ahumada-Cota; Armando Navarro-Ocaña; María E. Chávez-Berrocal; María E. Chávez-Berrocal; José Molina-López; José Molina-López; Luz M. Rocha-Ramírez; Armando Navarro-Cid del Prado; Carlos A. Eslava; Carlos A. Eslava (Frontiers Media S.A., 2023)
Worldwide, Urinary Tract Infections (UTIs) are an important health problem with many cases reported annually, women being the most affected. UTIs are relevant because they can become a recurrent condition, associated with different factors that contribute to the chronicity of the disease (cUTI). cUTI can be classified as persistent (peUTI) when the causative agent is the same each time the infection occurs or as reinfection (reUTI) when the associated microorganism is different. The purpose of this work was to characterize Escherichia coli isolates obtained in two prospective studies of patients with cUTI, to define which of them corresponded to peUTI and which to reUTI. A total of 394 isolates of E. coli were analyzed by agglutination with specific sera, antimicrobial susceptibility by diffusion disc test, and the phylogroups and presence of genes associated with virulence by PCR assays. Additionally, in some characterized strains adherence, invasiveness, and biofilm formation were analyzed by in vitro assays. The results showed that the peUTI strains belonged mainly to the classical UPEC serogroups (O25, O75, O6), were included in the B2 phylogroup, carried a great number of virulence genes, and were adherent, invasive, and biofilm-forming. Meanwhile, reUTI strains showed great diversity of serogroups, belonged mainly in the A phylogroup, and carried fewer virulence genes. Both peUTI and reUTI strains showed extensively drug-resistant (XDR) and multidrug-resistant (MDR) profiles in the antimicrobial susceptibility test. In conclusion, it appears that peUTIs are caused principally by classical UPEC strains, while reUTIs are caused by strains that appear to be a part of the common E. coli intestinal biota. Moreover, although both peUTI and reUTI strains presented different serotypes and phylogroups, their antimicrobial resistance profile (XDR and MDR) was similar, confirming the importance of regulating prophylactic treatments and seeking alternatives for the treatment and control of cUTI. Finally, it was possible to establish the features of the E. coli strains responsible for peUTI and reUTI which could be helpful to develop a fast diagnostic methodology.